Fundamental and Crucial Challenge in Tribology's: A Short Review - Norazlianie, Sazali (Akademi Baru, 2020)
Several studies have been accounted for the effect of wear, friction on machinery, manufacturing productivity, corrosion as well as costs. These principles and design advantages lead to a significant effect on a broad spectrum of contemporary applications including nanotechnology, alternative energies, biomedical and “green” methodologies. Many previous studies have been discussing the other mentioned applications; however, there is still a lack of literature that can be found related to the “green” tribology concept. Lately, the perception of tribology as science and technology has been applied since the tribological features of environmental, ecological balance likewise biological effects. This mini analysis might contribute to the fundamental, and primary challenge in tribology.